CHARACTERISTICS OF TASKS AND FUNCTIONS OF PROFESSIONAL TRAINING OF POLICE OFFICERS IN UKRAINE (Bulletin of criminological association of Ukraine, 2024)
The scientific article draws attention to the fact that the purpose of professional training of police officers is, firstly, the formation and maintenance of such a level of relevant knowledge, skills, and abilities in an amount sufficient for the effective performance of the functional tasks of the National Police; secondly, the formation of high moral and ethical (including patriotic) personality traits, which allows ensuring its activities through the prism of adherence to universal human values. The conclusion is made about the heterogeneity of professional training tasks, their dependence on a number of factors, in particular, on what exactly they are aimed at (what result), the subject and the specific sphere of their implementation. Therefore, it is advisable to group the tasks of professional training of police officers depending on their official status: 1) general (providing a holistic base of necessary knowledge, primarily of current legislation, physical, moral and ethical development, etc.); and 2) special, which are associated with the need for a person to perform additional functional powers, primarily in the field of management. Depending on the subject of professional training, for example, a police officer, whose tasks in the process of professional training are: obtaining a document certifying the completion of the relevant training; mastering the necessary knowledge and skills to perform professional duties; the possibility of career growth. Higher education institutions with specific training conditions have the task of organizing the educational process, scientific and methodological support, etc. It is substantiated that it is most appropriate to highlight the following key functions of professional training of police officers: didactic-methodological, cognitive, educational, socialization function, personal development, organizational, as well as the function of personnel support. It is these functions that most fully and meaningfully characterize the practical side of the relevant activity, as it seems.
Keywords: goal; tasks; functions; professional training; employees; National Police; police officers